Postnatal Serum Total Thyroxine of Very Preterm Infants and Long-Term Neurodevelopmental Outcome - Yung-Chieh Lin (Nutrients, 2021)
Primary congenital hypothyroidism is a disease associated with low serum thyroxine and elevated thyroid-stimulating hormone (TSH) levels. The processes of screening and treating congenital hypothyroidism, in order to prevent neurodevelopmental impairment (NDI) in newborns, have been well investigated. Unlike term infants, very preterm infants (VPIs) may experience low thyroxine with normal TSH levels (<10.0 μIU/mL) during long-stay hospitalization. In the current literature, thyroxine treatment has been evaluated only for TSH-elevated VPIs. However, the long-term impact of low thyroxine levels in certain VPIs with normal TSH levels deserves more research. Since July 2007, VPIs of this study unit received screenings at 1 month postnatal age (PNA) for serum TSH levels and total thyroxine (TT4), in addition to two national TSH screenings scheduled at 3–5 days PNA and at term equivalent age. This study aimed to establish the correlation between postnatal 1-month-old TT4 concentration and long-term NDI at 24 months corrected age among VPIs with serial normal TSH levels. VPIs born in August 2007–July 2016 were enrolled. Perinatal demography, hospitalization morbidities, and thyroid function profiles were analyzed, and we excluded those with congenital anomalies, brain injuries, elevated TSH levels, or a history of thyroxine treatments. In total, 334 VPIs were analyzed and 302 (90.4%) VPIs were followed-up. The postnatal TT4 concentration was not associated with NDI after multivariate adjustment (odd ratios 1.131, 95% confidence interval 0.969–1.32). To attribute the NDI of TSH-normal VPIs to a single postnatal TT4 concentration measurement may require more research.